Model Marketplace Berbasis Kearifan Lokal - Tarmizi, Tarmizi; Ismail, Ismail (Lembaga KITA, 2020)
This study aims to create a market model based on local wisdom so that the marketing activities of small businesses can run effectively. To prove the effectiveness of digital marketing media in the form of a marketplace, research subjects are needed, namely small businesses involved directly with online marketing, interview approaches, and their success rate in using digital media (marketplaces). Through this research, it is expected that small businesses can choose wisely and effectively the use of digital media (marketplaces) in their marketing activities so that their sales turnover can increase. The study took the location or object of research in the city of Banda Aceh. Considering that consumer behavior in the city of Banda Aceh is different from one another, of course, it must be measured and tested, whether the market model based on local wisdom can be applied and has a significant relationship to increase marketing activities and product sales of business actors. This type of research uses descriptive qualitative research, data analysis in the field of the research model and method is carried out by interviewing several SMEs and local marketplace users in the city of Banda Aceh. The sample in this study is small business practitioners who actively use the marketplace for the past two years in the process of marketing and selling their products in the online market. From the results of the non-random sampling, 173 respondents were generally employed, who were small businesses. Data collection techniques using interview and questionnaire models, and the analysis model used here is the Crosstabs Test. Based on the results of surveys and interviews with several business actors, it was found that there is a marketplace model based on local wisdom that has a very significant relationship in increasing the income of small businesses marketing and selling their products online in Banda Aceh City.Â Keywords: Marketplace, Small business actors, Local Wisdom